Control of LED Emission with Functional Dielectric Metasurfaces. Issue 1 (27th November 2019) - Khaidarov, Egor; Liu, Zhengtong; Paniagua‐Domínguez, Ramón; Ha, Son Tung; Valuckas, Vytautas; Liang, Xinan; Akimov, Yuriy; Bai, Ping; Png, Ching Eng; Demir, Hilmi Volkan; Kuznetsov, Arseniy I.
Abstract: The improvement of light‐emitting diodes (LEDs) is one of the major goals of optoelectronics and photonics research. LED integration to complex photonic devices requires precise control of the wavefront of the emitted light. Metasurfaces are spatial arrangements of engineered scatters that may enable this light manipulation capability with unprecedented resolution. Most of these devices, however, are only able to function properly under irradiation of laser light with a large spatial coherence. LEDs, on the other hand, have angularly broad, Lambertian‐like emission patterns characterized by a low spatial coherence, which makes the integration of metasurface devices on LEDs challenging. A novel concept for metasurface integration on LED is proposed, using a cavity to increase the LED spatial coherence through an angular collimation. The experimental demonstration of the proposed concept is implemented on a GaP LED architecture including a hybrid metallic‐Bragg cavity. By integrating a silicon metasurface on top, two different functionalities of these compact devices are demonstrated: directional LED emission at a desired angle and LED emission of a vortex beam with an orbital angular momentum. The presented concept is general, being applicable to other incoherent light sources and enabling metasurfaces designed for plane waves to work with incoherent light emitters. Abstract : A resonant cavity increases the spatial coherence of the LED source and transforms a Lambertian profile into a more planar‐like one, suitable for most of the current state of the art metasurfaces excitation. This allows for direct and compact metasurface and LED device integration. The diversity of possible functionalities is demonstrated on the beam deflection and orbital angular momentum generating devices.